Pengaruh Customer Rating, Customer Review, Dan Ease Of Use Terhadap Minat Beli Di Marketplace Shopee (Studi Kasus Pada Warga Kota Malang) - Lailatul Badria; Mohammad Rizal; Kartika Rose Rachmadi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research was conducted to determine the effect of customer ratings, customer reviews, and ease of use on buying interest in marketplace shopee (a case study in Malang city residents. This research is a quantitative study using primary data obtained by distributing questionnaires and measured using a Likert scale. The population in this study were residents of the city of Malang. The sample calculation in this study used the Malhotra formula which produced 75 respondents. The method of determining the sample was purposive sampling. The data analysis technique used SPSS 22. The results of this study were the variables customer rating, customer review, and ease of use has a simultaneous or partial effect on buying interest in the shopee marketplace. Keywords: Customer Rating, Customer Review, Ease Of Use And Purchase Intention